Determination of factors affecting post-partum depression in primary healthcare during the COVID-19 pandemic - Fitriana Kurniasari Solikhah; Nursalam Nursalam; Imam Subekti; Sri Winarni; Atti Yudiernawati (AOSIS, 2022)
Postpartum depression is a phenomenon that occurs in the first postpartum days. Symptoms of postpartum depression peak on days 3 to 5 postpartum with a duration ranging from a few hours to several days. Of course, this will be different during the Covid-19 pandemic. The aim of this study was to analyze the determinants that influence the incidence of post-partum depression in primary health during the pandemic. The method in this research is descriptive analysis with cross sectional approach with a total sample of 100 respondents. The research instrument used a standard instrument, namely the EPDS (Edinburgh Postnatal Depression Scale) instrument. The results of the study were the determinant factors of parity in primigravida and attitudes. From the results of this study, it can be concluded that the dominant factors that greatly influence the risk of post-partum depression in women in primary health during the pandemic are parity (primigravida) and the attitude of women who take it for granted when they know that they are at risk of post-partum depression.